2014
DOI: 10.1111/tct.12192
|View full text |Cite
|
Sign up to set email alerts
|

Can we improve the delivery of bedside teaching?

Abstract: The new method, using protected clinical teaching time at a specific scheduled weekly time, and using opportunistically available junior clinicians, is perceived by students as superior to the old method of one constant, experienced tutor allocated to a group. The main obstacles [to bedside teaching] are: the availability of clinical tutors and access to suitable patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 6 publications
3
12
0
Order By: Relevance
“…Interestingly, the minority of students (8.9%) who said that they trust junior doctors more stated that this is because juniors are often ‘more up to date’ with knowledge and more aware of assessment requirements. This is in keeping with existing literature …”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Interestingly, the minority of students (8.9%) who said that they trust junior doctors more stated that this is because juniors are often ‘more up to date’ with knowledge and more aware of assessment requirements. This is in keeping with existing literature …”
Section: Discussionsupporting
confidence: 92%
“…Students reported a desire to impress consultants, but found that inconsistency in the teaching delivered by consultants made it more challenging than that delivered by juniors, who students perceived as being more standardised in their teaching approach. Some students perceived that juniors are more familiar with the current curriculum and assessment requirements, whereas consultants may wish to discuss topics that are not part of the student curriculum, a finding that is in agreement with existing literature . Students who reported no difference in how challenged they felt stated that this depends more on the interpersonal attributes of the teacher, and how well they engage with students and the teaching process.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…This literature has highlighted important aspects of clinical supervisors' role in bedside teaching: a consistent decline in the occurrence of bedside teaching [12][13][14], perceived challenges and barriers to bedside teaching [8,10,15,16], perceived and measured benefits of bedside teaching [8,11], the increasing role of patients and peers in bedside teaching [8,17], and specific strategies to improve bedside teaching [9,11,18,19]. However, these studies have focused narrowly on 1 aspect of the educational role of the clinical supervisors and do not reflect other important supervisors' responsibilities in the clinical environment, such as being a role model, providing access to authentic clinical activities, and offering clinical guidance.…”
Section: Introductionmentioning
confidence: 99%